A density functional theory study of the reconstruction of gold (111) surfaces (2014)
We studied (p × √3) gold (111) surface reconstructions within the DFT/PW91 approximation. Our findings clearly show that the reconstruction is energetically favorable in unreconstructed surfaces equal to or larger than the unit cell of the final reconstructed surface. Reconstructions in surfaces smaller than ∼2.95 nm in the [11̄0] direction are not more stable than the unreconstructed surface, and this may explain why (p × √3) type reconstructions have not been observed in subnanometer gold particles. We found that reconstructions with (22 × √3) and (23 × √3) unit cells, usually reported in experiments, are isoenergetic. © 2014 American Chemical Society.